A new history of modern Latin America - Clayton, Lawrence A.; Conniff, Michael L.; Gauss, Susan M., 1968- (University of California Press, 2017)
"This comprehensive text provides a detailed narrative history of each of the nations of Latin America, from Chile and Argentina in the South to Mexico and Cuba in the north. It begins with the Wars of Independence in the early nineteenth century and stretches to the democratic turn in the twenty-first. It interprets major themes, such as the age of caudillos in the nineteenth century, populism in the twentieth century, and globalization in the twenty-first century. These themes, along with others such as ethnic strife, social revolutions, and militarism, transcend borders and show the unity of the Latin America experience, even as the text draws out the diversity that marks the region's geography, peoples, and cultures."--Provided by publisher